The impact of numerical expenditure rules on budgetary discipline over the cycle - Fédéric Holm-Hadulla; Sebastian Hauptmeier; Philipp Rother (European Central Bank (ECB), 2010)
We study the impact of numerical expenditure rules on the propensity of governments to deviate from expenditure targets in response to surprises in cyclical conditions. Theoretical considerations suggest that due to political fragmentation in the budgetary process expenditure policy might be prone to a pro-cyclical bias. However, this tendency may be mitigated by numerical expenditure rules. These hypotheses are tested against data from a panel of EU Member States. Our key findings are that (i) deviations between actual and planned government expenditure are positively related to unanticipated changes in the output gap, and (ii) numerical expenditure rules reduce this pro-cyclical bias. Moreover, the pro-cyclical spending bias is found to be particularly pronounced for spending items with a high degree of budgetary flexibility.
Keywords: C23; E62; H50; 330; expenditure rules; fiscal discipline; spending bias; stabilisation; Öffentliche Ausgaben; Finanzpolitik; Haushaltsplanung; Haushaltsplanung; Haushaltskonsolidierung; EU-Staaten